The Regulatory Roles of Long-non-Coding RNAs in Chemotherapy-Resistant Metastatic Breast Cancer - Saeid Ghorbian; Arezo Zaree; Elnaz Khojasteh (Fasa University of Medical Sciences, 2020)
Currently, breast cancer is the most prevalent malignancy worldwide, with the largest prevalence and mortality among women. The invasion and metastasis are the main causes of death from malignancies. However, the main mechanism of invasion and metastasis is not thoroughly understood. lncRNA is a large class of non-coding transcripts that have more than 200 bases length and cannot encode a protein. Evidence suggests that lncRNA regulates gene expression at epigenetic, transcription, and post-transcriptional levels. In addition, they are involved in several biological process, including cell proliferation, apoptosis, invasion, metastasis, and angiogenesis. Chemotherapy resistance is one of the major barriers to breast cancer that limits the effects of targeted and common therapies in clinical settings. Therefore, understanding the underlying mechanisms of drug resistance is necessary to develop strategies to bypass resistance in patients with breast cancer. Several published reports show that lncRNAs play an important role in regulating cell division and provide cells with a drug-resistant phenotype through different manners. The knowledge gained from this review can help to provide new strategies for clinical diagnosis and prevention and reduction of drug resistance in chemotherapy.